TIGIT‐expressing zoledronate‐specific γδ T cells display enhanced antitumor activity. Issue 6 (10th November 2022) - You, Hongqin; Zhu, Huifang; Zhao, Yajie; Guo, Jindong; Gao, Quanli
Abstract: Human γδ T cells hold a pivotal role in tumor immunosurveillance through their prompt activation and cytokine secretion and have received much attention in adoptive immunotherapy of clear cell renal cell carcinoma (ccRCC). However, the therapeutic effects are limited in ccRCC. Therefore, it is now critical to improve therapeutic strategies based on γδ T cells, especially identification of functional γδ T cell subsets. In this study, we aimed to identify γδ T cells that might have enhanced responses against ccRCC. Bioinformatic analysis showed that ccRCC patients with high T cell immunoglobulin and immunoreceptor tyrosine‐based inhibitory motif domain (TIGIT) expression had higher levels of effector molecules. Then, we examined the changes in the TIGIT + γδ T cell percentages of 6 ccRCC patients and 14 healthy subjects through zoledronate (ZOL) stimulation. Results indicated that percentages of TIGIT + γδ T cells were positively correlated with activated γδ T cells in early activation stage. Further study demonstrated that TIGIT + γδ T cells exhibited enhanced activation, contained more terminally differentiated effector γδ T cells and produced higher cytokine compared with TIGIT ‐ γδ T cells. Finally, we investigated the functions and found that TIGIT + γδ T cells exhibited stronger tumor reactivities and higher cytotoxicity when challenged by tumor cells. Above results imply that TIGIT + γδ T cells are the main effectors in ZOL recognition and tumor cells challenging. The results of the present study serve as basis for future functional studies on TIGIT + γδ T cells and provide a promising approach of immunotherapy in ccRCC. Graphical Abstract: TIGIT expressing, ZOL‐specific γδ T cells are not exhausted, but more functional in antitumor immune response.